Cd11b+ myeloid cells support hepatic metastasis through down‐regulation of angiopoietin‐like 7 in cancer cells. Issue 2 (6th May 2015) - Lim, Su Yin; Gordon‐Weeks, Alex; Allen, Danny; Kersemans, Veerle; Beech, John; Smart, Sean; Muschel, Ruth J.
<x xml:space="preserve">Abstract</x> Myeloid cells are known to mediate metastatic progression. Here, we attempted to elucidate the mechanisms underlying these effects by identifying gene expression alterations in cancer cells forming hepatic metastases after myeloid cell depletion. Hepatic metastases are heavily infiltrated by CD11b+ myeloid cells. We established hepatic metastases in transgenic CD11b‐diphtheria toxin receptor mice by intrasplenic injection of MC38 colon and Lewis lung carcinoma cells before depleting myeloid cells with diphtheria toxin. Myeloid cell depletion inhibited metastatic growth with a marked diminishment of tumor vasculature. Expression of ANGPTL7 (angiopoietin‐like 7), a protein not previously linked to metastasis, was highly up‐regulated in cancer cells after myeloid cell depletion. This effect was duplicated in tissue culture, where coculture of cancer cells with tumor‐conditioned myeloid cells from liver metastases or myeloid cell conditioned media down‐regulated ANGPTL7 expression. Analogous to myeloid cell depletion, overexpression of ANGPTL7 in cancer cells significantly reduced hepatic metastasis formation and angiogenesis. We found that ANGPTL7 itself has strong antiangiogenic effects in vitro. Furthermore, analysis of The Cancer Genome Atlas colorectal and breast cancer data sets revealed striking ANGPTL7 underexpression in cancerous compared to normal tissues. Also, ANGPTL7 was down‐regulated in metastatic liver colonies of colorectal cancer patients compared to their adjacent liver tissue. Conclusion: Myeloid cells promote liver metastasis by down‐regulating ANGPTL7 expression in cancer cells; our findings implicate ANGPTL7 as a mediator of metastatic progression and a potential target for interference with liver metastases. (Hepatology 2015;62:521–533